Trends in Cesarean Delivery at a Tertiary Care Hospital - Ojha, Neebha; Khaniya, Bishal; Pun, Sunita; Bhansakarya, Rakina; Ghimire, Asmita; Sharma, Ashish (Journal of Institute of Medicine Nepal, 2025)
Introduction Cesarean delivery is on the rise globally, and many government bodies and clinicians have expressed concern about the rising rate of cesarean delivery. The study aims to assess the trend in cesarean delivery rate and the type of cesarean delivery at five-year intervals during the study period. Methods This descriptive cross-sectional study was conducted at TU Teaching Hospital by a chart review of cesarean delivery (CD) during the years 2014, 2019, and 2024 AD. Basic data including age, parity, ethnicity, gestational age, and multiple pregnancy was obtained. The collected data were entered and analyzed in SPSS 26. Results The annual CD rate was 39.0 %, 52.7%, and 56.0% among the total livebirth delivery during the years 2014, 2019, and 2024, respectively. The proportion of primary CD increased from 2014 to 2019 but remained static in 2024 (31%, 41%, and 39.4%), however for repeat CD it increased steadily. Mothers undergoing CD in the age ≥35 years increased from 106 (6.1%) in 2014 to 241 (13.5%) in 2024 (8%, 11.7%, and 16.5%). The emergency CD were three times more common than elective CD in all the years interval. The most common indications for the primary and repeat CD were a fetal distress and refused trial of labor respectively. Conclusions This study showed increasing trend in the cesarean delivery rate. Primary CD constituted more than the repeat CD, however the rate of increase was more in the repeat than in the primary CD. It is important to reduce primary CD if we want to decrease the overall CD rate.